Optimalisasi Potensi Lingkungan Melalui Pembuatan Vertical Garden dan Pengolahan Limbah Organik - Lilis Khotjiah; Annisa Maulidya Wijayanti; Asri Melani; Berlin Miralda Ramadhani; Muhammad Dimas Permana; Mohamad Nur Alief; Rismawati Rismawati; Amelia Fitrianaldi; Andhika Prasetiadji; Ainiyah Miskiyah; Febrina Chairunisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
This year's Student Community Service was held in domicile areas of each student due to the Covid-19 pandemic. Purpose of this activity is to create innovation and community independence through the use of land as vertical garden for farming and utilization of organic waste. This activity was held in the July-August 2020 located in RW 12, Kedung Badak Village, Tanah Sareal District, Bogor City. All activities were carried out for approximately 5 weeks and each week conducted field visits to RW 12. Implementation of program done by obey the health protocol rules. The entire program that has been implemented running very well and welcomed by the residents. Many residents gave positive responses to the programs implemented and hoped that it could be carried out in a sustainable manner. The partner of this activity, Karang Taruna RW 12, is also satisfied and enthusiastic about implementing the program. Keywords: waste, vertical garden, Kedung Badak